Symbolic computation of exact solutions for fractional differential-difference equation models - Aslan, Ismail (Nonlinear Analysis: Modelling and Control, 2015)
The aim of the present study is to extend the G’/G-expansion method to fractional differential-difference equations of rational type. Particular time-fractional models are considered to show the strength of the method. Three types of exact solutions are observed: hyperbolic, trigonometric and rational. Exact solutions in terms of topological solitons and singular periodic functions are also obtained. As far as we are aware, our results have not been published elsewhere previously.